BALANCED SCORECARD SEBAGAI KONSEP PENGUKURAN KINERJA PERBANKAN - PUSPITA DEWI, NATALIA Puspita (Jurnal Akuntansi AKUNESA, 2013)
Management system implemented by the banking system is currently more focused onfinancial performance as measured periodically by using financial measures. Bankingbusiness competition would also have to change the method of performance appraisal areused by banks to measure their performance. Assessment of performance is critical for banks.By conducting performance appraisals, banks can determine the level of achievement duringthe given period.Therefore, in a performance assessment of banking required balance(balanced) between the financial and non financial. For that developed the concept of nonfinancialperformance measures that can measure the success of banks in realizing its longtermstrategies so that banks can win the business competition.In the measurement of the fourperspectives, namely: the financial perspective, customer perspective, internal businessprocess perspective, as well as learning and growth perspective. Balance between thescorecard from each perspective to determine the performance improvement of bankingdoubled. To anticipate changes in the banking business environment and competition, thebank requires a solid foundation in formulating the vision and mission in the form ofintegrated strategic planning through the balanced scorecard.Keywords:PerformanceMeasurement, BalancedScorecard, Banking.